Ageing in the right place—usability of a web-based housing counselling service - Frida Nordeström; Marianne Granbom; Susanne Iwarsson; Magnus Zingmark (Scandinavian Journal of Occupational Therapy)
Introduction Residential reasoning is a complex process that includes decisions on whether to age in place or to relocate. Ageing in the Right Place (ARP), a web-based housing counselling service was created to support older adults in this process. The study’s aim was to evaluate the usability of the ARP as regards content, design, specific functions, and self-administration as a mode of delivery and to lay the ground for further optimisation.Material and method Nine women and five men (aged 66–82) completed a series of tasks using the ARP. Qualitative and quantitative usability data were collected through online interviews. Data were analysed using qualitative content analysis and descriptive statistics.Results Experiences of the specific functions, content, and design of the ARP were described as mainly positive. Additions to the content and optimisation to assist in the general navigation of the website were suggested. The participants disagreed regarding the preferred mode of delivery, which indicates a need for selectable options. A system usability scale median score of 84 indicated acceptable usability.Conclusion The ARP seems to have acceptable usability, which paves the way for further evaluation.Significance By enabling residential reasoning, older adults are supported to make proactive choices based on informed decisions.